Kandungan Fitokimia dan Bioaktivitas Ekstrak Metanol Biji Palem Putri (Veitchia merillii) - adawiah adawiah (Syarif Hidayatullah State Islamic University, 2016)
Palem putri (Veitchia merillii) is a kinds of Araceae plant which has been used by the community in cure myopic eyes and for woman who have pregnant. However, research on the content of secondary metabolites and bioactivity of palm putri has never been done. This study aims to determine the phytochemical content, total polyphenols and flavonoids and bioactivity include antioxidant activity DPPH free radical scavenging, antidiabetic method alpha-glucosidase enzyme inhibition and toxicity of the methods Bhrine Shrimp Lethal Test (BSLT). Palem putri contains secondary metabolites, alkaloids, flavonoids, terpenoids, polyphenols, phenolic hydroquinone and saponins. The methanol extract of palm putri seed has a total polyphenol content and total flavonoids respectively 642.8 mg gallic acid / gram sample extract and quercetin 543.3 mg / gram sample extract, has a very strong antioxidant activity with IC50 value of 0.82 ppm, the level of toxicity is very toxic with LC50 values ​​of 11.535 ppm. As well as having antidiabetic activity using the enzyme alpha-glucosidase inhibition with IC50 values ​​of 1.97 ppm is even higher than the activity of the compound quercetin as a positive control. Keywords: Palem putri, bioactivity, antioxidant, antidiabetic, toxicity Palem putri (Veitchia merillii) is a kinds of Araceae plant which has been used by the community in cure myopic eyes and for woman who have pregnant. However, research on the content of secondary metabolites and bioactivity of palm putri has never been done. This study aims to determine the phytochemical content, total polyphenols and flavonoids and bioactivity include antioxidant activity DPPH free radical scavenging, antidiabetic method alpha-glucosidase enzyme inhibition and toxicity of the methods Bhrine Shrimp Lethal Test (BSLT). Palem putri contains secondary metabolites, alkaloids, flavonoids, terpenoids, polyphenols, phenolic hydroquinone and saponins. The methanol extract of palm putri seed has a total polyphenol content and total flavonoids respectively 642.8 mg gallic acid / gram sample extract and quercetin 543.3 mg / gram sample extract, has a very strong antioxidant activity with IC50 value of 0.82 ppm, the level of toxicity is very toxic with LC50 values ​​of 11.535 ppm. As well as having antidiabetic activity using the enzyme alpha-glucosidase inhibition with IC50 values ​​of 1.97 ppm is even higher than the activity of the compound quercetin as a positive control. Keywords: Palem putri, bioactivity, antioxidant, antidiabetic, toxicity DOI: http://dx.doi.org/10.15408/jkv.v2i1.3076